1988
DOI: 10.1063/1.341600
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature GaAs epitaxial growth using electron-cyclotron resonance/metalorganic-molecular-beam epitaxy

Abstract: A low-temperature GaAs epitaxial growth method called electron-cyclotron resonance molecular-beam epitaxy was newly developed. Triethylgallium (TEGa) and triethylarsine (TEAs) were used as source gases and were introduced without thermal decomposition. The method has the advantage of cleaning the GaAs substrate at the growth temperature just prior to growth as well as to decompose metalorganics with the hydrogen plasma activated by the cyclotron resonance. The epitaxial GaAs film was successfully grown at a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These values are in agreement with calculations made with an analytical model. 44 According to measurements of Trainor et al 73 for the pressure range considered in our work the volume recombination of hydrogen atoms can be neglected. The decrease of the recombination fraction with increasing distance from the hydrogen atom source is then ascribed to wall losses of atomic hydrogen.…”
Section: F Substrate Temperature Effectsmentioning
confidence: 99%
“…These values are in agreement with calculations made with an analytical model. 44 According to measurements of Trainor et al 73 for the pressure range considered in our work the volume recombination of hydrogen atoms can be neglected. The decrease of the recombination fraction with increasing distance from the hydrogen atom source is then ascribed to wall losses of atomic hydrogen.…”
Section: F Substrate Temperature Effectsmentioning
confidence: 99%
“…Although conventional thermal cleaning can remove the oxide layer, this can also lead to surface roughness 3,4 and accumulation of impurities. 5,6 On the other hand, it has been shown that exposure of the surface to a hydrogen plasma [7][8][9][10][11] or hydrogen, in atomic or radical form, [12][13][14] produces clean GaAs surfaces. In particular, the removal of oxides and contaminants is successful at moderate temperatures ͑200-500°C͒, considerably lower than thermal desorption temperatures.…”
mentioning
confidence: 99%